Hybrid centralised MAC protocol for reliable broadcast of safety messages in vehicular ad hoc network. (2018) - Boulila, Narjes; Hadded, Mohamed; Laouiti, Anis; Saidane, Leila Azouz
Several medium access control (MAC) protocols were proposed to provide high-performance for vehicular ad hoc network (VANET). For instance, the contention-free MAC allows several vehicles to share the same communication channel. However, contention-based MAC protocols do not require any predefined schedule where each node competes for channel access when it needs to transmit data without any guarantee of success transmission. Hence, a hybrid MAC protocol that adopts time division multiple access (TDMA) and carrier sense multiple access (CSMA/CA) is required to enhance the network performance. Nevertheless, hybrid MAC protocols cannot ensure services differentiation so that critical messages and non-security messages have the same priority. To overcome such limitation, this paper focuses on the design of a novel access method integrating TDMA and enhanced distributed channel access (EDCA) in unique architecture called QoS-aware centralised hybrid MAC protocol (QCH-MAC). To prove the efficiency of our proposal, the latter was implemented in ns-3.